Learner Motivation in Arabic Language Acquisition: A Review of Theoretical and Empirical Studies - Muhammad Ghazali; Muhammad Mirzan; Fitri Hidayati; Gusti (JISRev: Journal of Islamic Studies Review, 2026)
This study aims to examine learner motivation in Arabic language acquisition through a comprehensive literature review of theoretical and empirical studies published between 2020 and 2025. Motivation is widely recognized as a key factor influencing learners’ engagement, persistence, and achievement in second language learning. The study employs a thematic analysis to synthesize findings from selected peer-reviewed articles, focusing on motivational dimensions, socio-cultural influences, pedagogical practices, and technological integration. The results indicate that motivation in Arabic language learning is multidimensional, encompassing intrinsic, extrinsic, integrative, and instrumental orientations. Religious and cultural factors are found to play a dominant role, particularly in Muslim contexts, while pedagogical innovation and technology-enhanced learning significantly contribute to increased learner engagement. However, challenges such as language complexity, limited instructional resources, and technological disparities continue to affect motivation levels. The study highlights the importance of adopting context-sensitive and student-centered approaches to enhance motivation and improve learning outcomes. It also identifies research gaps, particularly the need for longitudinal and context-specific studies. Overall, this study provides insights into effective strategies for fostering motivation in Arabic language education.